A T-algebraic approach to primal-dual interior-point algorithms - Chua, Chek Beng. (2009)
Three primal-dual interior-point algorithms for homogeneous cone programming are presented. They are a short-step algorithm, a large-update algorithm, and a predictor-corrector algorithm. These algorithms are described and analyzed based on a characterization of homogeneous cones via T-algebras. The analysis shows that the algorithms have polynomial iteration complexity